Vulnerabilities of wheat crop farmers in war zone - Noor, Stanikzai Ahmad; Ali, Fazlin; Kamarulzaman, Nitty Hirawaty (Rynnye Lyan Resources, 2021)
Wheat is the staple food crop in Afghanistan and maintaining its production plays important role in ensuring food security and food self-sufficiency. Wheat and its products are accounted for almost 60% to 75% of calories intake. However, being a country that has been facing war since 1978, it has been challenging for the wheat production industry to maintain its production to feed its people. Hence, the purpose of this study is to investigate wheat crop industry players’ vulnerabilities in the production of the wheat crop in a prolonged war zone. The study is conducted through the case study approach. Required data was collected through interviews, observations and documents which was analyzed through thematic analysis. This study found that in addition to the normal vulnerabilities/issues faced by the wheat crop industry players in the world, the players in the war zone have to face psychological effects, and financial corruption as well.